-18=1-3a-4

Simple and best practice solution for -18=1-3a-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=1-3a-4 equation:


Simplifying
-18 = 1 + -3a + -4

Reorder the terms:
-18 = 1 + -4 + -3a

Combine like terms: 1 + -4 = -3
-18 = -3 + -3a

Solving
-18 = -3 + -3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
-18 + 3a = -3 + -3a + 3a

Combine like terms: -3a + 3a = 0
-18 + 3a = -3 + 0
-18 + 3a = -3

Add '18' to each side of the equation.
-18 + 18 + 3a = -3 + 18

Combine like terms: -18 + 18 = 0
0 + 3a = -3 + 18
3a = -3 + 18

Combine like terms: -3 + 18 = 15
3a = 15

Divide each side by '3'.
a = 5

Simplifying
a = 5

See similar equations:

| lg(3x-2)=-1 | | 4x=8+y | | (9x+6)-(4x^2+2x+3)= | | 6.5=2.5r-12 | | (2y-10)+2x=82 | | -30=p/12 | | y=3x^2-5x+1 | | 25=-2w | | 8v=2*(4v+2) | | 4x^3+16x=0 | | 25v-4v+8=4 | | 2y-10+2x=p | | y=2x^2+4x+2 | | 4r-3r-1=4 | | 7x-3*2=x | | 0=-16t^2+76t+46 | | 4x+x-4=2 | | 2x-5/2-4/5 | | 9-7(2)^3/(-8) | | 8-3(3)^3/(-27) | | 0=-16t^2+26t+100 | | 15-2.5h=4h | | (2+2)^2/(5-3)^2 | | 2b+3b-13=-3 | | 2n-3n+1=5 | | b^2-4ac=-3 | | 3x+2=3(x+8) | | 21x-28-15x-25=7x-70 | | 18=-a | | 2m+3=142 | | 2x-5/3=11 | | 83/12-31/4 |

Equations solver categories